Institutional Investor Attention, Agency Conflicts, and the Cost of Debt - El Ghoul, Sadok; Guedhami, Omrane; Mansi, Sattar A.; Yoon, Hyo Jin (Management Science, 2023)
Using a new measure of shareholder inattention constructed from exogenous industry shocks to institutional investor portfolios, we find that firms with distracted shareholders are associated with a higher cost of debt. This effect is stronger for firms with more powerful CEOs, firms with higher information asymmetry, and those operating in less competitive product markets. Further testing suggests that the inattention-cost of debt relation is driven primarily by dual holders directly observing shareholder distraction. Our results are robust to controlling for inattention at the retail investor level and to other external monitors, including credit rating agencies, financial analysts, and Big 4 auditors. Overall, our evidence suggests that institutional shareholder inattention has an incrementally negative effect on bond pricing. This paper was accepted by Brian Bushee, accounting. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4593 .